Facile Detection of Light-Controlled Radical Scavengers from Natural Products Using In Situ UV-LED NMR Spectroscopy - InWha Park; Goeun Park; Yoojin Choi; Seung-Woo Jo; Hak Cheol Kwon; Jin-Soo Park; Jin Wook Cha (Antioxidants, 2022)
With the recent development of chemical analysis technology, attention has been placed on natural light-sensitive compounds that exhibit photoreactivity to expand the structural diversity of natural product chemistry. Photochemical reactions that proceed via a free radical mechanism could be used to modulate the radical-scavenging ability of natural products as well as involve structural change. As the health benefits of radicals are also presented, there is a need for a controllable radical scavenging method for topical and selective application. In this study, we developed a novel acquisition and processing method to identify light-controlled radical scavengers in plant extracts and evaluate their antioxidant activity under light irradiation based on in situ UV-LED NMR spectroscopy. Using the developed method, licochalcones A and B, in which the trans and cis isomers undergo reversible photoisomerization, were selectively identified from licorice root extract, and their light-induced free radical scavenging activity was confirmed.